Real Time Distributed and Decentralized Peer-to-Peer Protocol for Swarm Robots - RABBAH, Mahmoud Almostafa; RABBAH, Nabila; BELHADAOUI, Hicham; RIFI, Mounir (International journal of advanced computer science & applications, 2021)
This contribution proposes an approach to enhance the capability of robotic agents to join the Internet of Things (IoT) and act autonomously in extreme and hostile environment. This capability will help in the development in environments where the connectivity, availability, and responsivity of the devices are subject to variations and noises. A real time distributed and decentralized Peer-to-Peer protocol was designed to allow Autonomous Unmanned Surface Vessels (AUSV) extend their context awareness. The developed Middleware allows a real time communication and is designed to run on top of a Real Time Operating System (RTOS). Furthermore, the proposed Middleware will give researchers access to a large amount of data collected by sensors, and thus solve one of the major problems encountered while training artificial intelligence models which is the lack of sufficient data.